The suitability of implementing 3D printing construction towards Malaysian construction industry / Harith Nasir and Fairiz Miza Yop Zain - Nasir, Harith; Yop Zain, Fairiz Miza (2023)
3D printing will change the construction industry's routine. 3D printing uses a computer to layer liquid substance to form a building's shape. Thus, this research is aimed to determine the suitability of the implementation of 3D printing construction in the Malaysian construction industry. The research's two objectives are (1) to identify the challenges; and (2) to analyze construction industry players' capabilities implementing 3D Printing construction. This quantitative method will be utilized by distributed questionnaires to Quantity Surveyors at QS firm and Contractor G7 in Petaling district, Selangor. The findings showed that they are aware of the challenges of implementing 3D printing construction in the Malaysian construction industry due to a lack of materials, machinery, skills, and environmental impact. Construction players in Malaysia recognise their inability to understand 3D Printing construction. In conclusion, Malaysian construction players are unable to comprehend the 3D Printing construction concept, so 3D Printing construction cannot be implemented yet.